Moringa oleifera Lam and its Therapeutic Effects in Immune Disorders - Xiao, Xiao; Wang, Jue; Meng, Chen; Liang, Weibo; Wang, Tao; Zhou, Bin; Wang, Yanyun; Luo, Xiaolei; Gao, Linbo; Zhang, Lin (Frontiers in Pharmacology, 2020)
Moringa oleifera Lam., a plant native to tropical forests of India, is characterized by its versatile application as a food additive and supplement therapy. Accumulating evidence shows that Moringa plays a critical role in immune-related diseases. In this review, we cover the history, constituents, edibility, and general medicinal value of Moringa. The effects of Moringa in treating immune disorders are discussed in detail. Moringa can not only eliminate pathogens, including bacteria, fungi, viruses, and parasites, but also inhibit chronic inflammation, such as asthma, ulcerative colitis, and metabolic diseases. Additionally, Moringa can attenuate physical and chemical irritation-induced immune disorders, such as metal intoxication, drug side effects, or even the adverse effect of food additives. Autoimmune diseases, like rheumatoid arthritis, atopic dermatitis, and multiple sclerosis, can also be inhibited by Moringa. Collectively, Moringa, with its multiple immune regulatory bioactivities and few side effects, has a marked potential to treat immune disorders.